2008
DOI: 10.1016/j.jtcvs.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Borderline hypoplasia of the left ventricle in neonates: Insights for decision-making from functional assessment with magnetic resonance imaging

Abstract: Magnetic resonance imaging is feasible in neonates with borderline left ventricular hypoplasia. Echocardiography does not accurately measure left ventricular hypoplasia in these patients and may unfairly preclude some patients from a biventricular repair in whom magnetic resonance is reassuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 34 publications
3
79
1
1
Order By: Relevance
“…4,8 However, even when using risk stratification scores, deciding which ventricles will be able to perform systemic work continues to be problematic. 9 MRI summation of discs has been applied to measure LV volumes in these young patients.…”
Section: Clinical Perspective On P 742mentioning
confidence: 99%
See 2 more Smart Citations
“…4,8 However, even when using risk stratification scores, deciding which ventricles will be able to perform systemic work continues to be problematic. 9 MRI summation of discs has been applied to measure LV volumes in these young patients.…”
Section: Clinical Perspective On P 742mentioning
confidence: 99%
“…9 MRI summation of discs has been applied to measure LV volumes in these young patients. 4 However, MRI scans may require general anesthesia, and in some instances mechanical venti-lation, and involve a series of breath holds that may be associated with hemodynamic compromise in some of these very ill infants.…”
Section: Clinical Perspective On P 742mentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, additional imaging using CMR is necessary to clarify details of intracardiac or extracardiac vascular anatomy, quantify ventricular volume for "borderline" sized ventricles, and to evaluate for the presence of endomyocardial fibroelastosis. 60,61 Diagnostic cardiac catheterization is rarely necessary in the newborn period. Traditionally, cardiac catheterization is performed before the cavopulmonary anastomosis and the Fontan operation.…”
Section: Evaluation Of the Functionally Single Ventriclementioning
confidence: 99%
“…For example, we recently showed that functional MRI-based flow studies allowed a biventricular repair in up to one-third of neonates with marginal-size left ventricles who might have otherwise undergone a single ventricle repair. 13 Although not perfect, functional data increase the accuracy and compress the confines of the marginal zone for binary decisions. The error rate for acute tolerances of VSD closure in this study was 5.2% (1/19), and the statistical predictive value of the flow study was 83%.…”
Section: Relevance Of the Datamentioning
confidence: 99%